Assembling payments for ecosystem services in Wales - Sophie Wynne-Jones; Vetter, Thomas (London : Routledge, 2018)
This chapter uses an assemblage approach to evaluate the development of ‘payments for ecosystem services’ in Wales, via transformations of agri-environmental governance over the last ten years. Whilst the adoption of PES has led to a shift in governance style and State responsibilities that echoes broader trends in neoliberalisation, we reject readings of hybrid neoliberalism following, instead, Tania Murray Li’s (2006) practices of assemblage to unpick the complex institutional arrangements emerging. Using an assemblage approach enables us to assess how different actors are mobilising and aligning around the PES approach to advance their own agendas. Following the practices used to authorise and render their concerns technical then shows us how and why some actors are being marginalised in this process, particularly as failures emerge and re-assembling is undertaken. Finally, we offer insights on how the State continues to maintain power whilst entering into new relations with other actors, advancing a more experimental mode of governance. The empirical material is based on three qualitative case studies, including pan-Wales agri-environment schemes as well as the ‘Pumlumon Project’ in Mid-Wales and the ‘Ecosystem Enterprise Partnership – Ecobank’ in South-Wales.